The Protective Effect of Antioxidant Enriched Fractions from Colored Potatoes Against Hepatotoxic Oxidative Stress in Cultured Hepatocytes and Mice. Issue 1 (8th August 2016) - Kim, Da Hye; Kim, Myungsuk; Oh, Sang‐Bin; Lee, Kyung Mi; Kim, Sang Min; Nho, Chu Won; Yoon, Won Byong; Kang, Kyungsu; Pan, Cheol‐Ho
Abstract: Herein, we prepared standardized antioxidant‐enriched fractions from red (AFR) and purple (AFP) colored potatoes and evaluated their protective effects against hepatotoxicity induced by oxidative stress. The major compound contained in both AFR and AFP was 5‐caffeoylquinic acid. Experiments in vitro showed that AFR and AFP protected against HepG2 cell death induced by tert ‐butyl hydroperoxide ( t ‐BHP) as determined by cell viability assay. AFR and AFP recovered alanine aminotransferase (ALT) and aspartate aminotransferase (AST) enzyme activities, which increased by t ‐BHP treatment in HepG2 cells. AFR and AFP also inhibited the cleavage of PARP and caspase‐3 in HepG2 cells. Moreover, in vivo experiments in mice showed that AFR and AFP protected against t ‐BHP‐induced hepatotoxicity and recovered serum ALT and AST enzyme activities. AFR and AFP also rescued serum antioxidant enzyme activities, catalase and glutathione peroxidase, which were disturbed by t ‐BHP treatment. Our data clearly demonstrate that AFR and AFP protect against hepatic damage induced by oxidative stress. Practical Applications: Colored potatoes contain plentiful amounts of antioxidant compounds that can be developed into dietary supplements for the improvement of human health. We prepared antioxidant‐enriched fractions from red and purple colored potatoes (AFR and AFP, respectively) to be used as hepatoprotective agents. Based on chemical profiling analysis, we found that 5‐caffeoylquinic acid can serve as a marker for the standardization of AFR and AFP as functional food materials. AFR and AFP strongly protected against oxidative stress and injury both in cultured hepatocytes and mice. AFR and AFP prevented the cell death of hepatocytes, and they also rescued hepatic damage markers ALT and AST both in cell and animal experiments. Generally, AFP showed higher hepatoprotective activity than AFR. Taken together, AFR and AFP may be promising candidates as functional foods for improving human liver function.